Класифікація ключових слів семантичного ядра веб-спільноти - Слобода, Катерина (Видавництво Львівської політехніки, 2012)
Keywords that are part of the same semantic class can replace each other in the process search. That is, if the user requests contain one of the keywords, the search will be issuing all posts that contain the keywords of this class. This approach allows increasing the percentage of completeness and accuracy of search.
Keywords: класифікація ключових слів; класифікація тем підфорумів; семантичне ядро; точність пошукової видачі; класи семантичного ядра; повнота пошукової видачі